DESIGN AND ANALYSIS OF COMB SHAPE MICROSTRIP PATCH ARRAY ANTENNA FOR WLAN APPLICATIONS - B Ramya; C Supratha; S Robinson (ICTACT Journal on Communication Technology, 2018)
A comb shape rectangular slotted 1 X 4 microstrip patch array antenna is proposed and designed for wireless local area network applications. The functional parameters of the antenna namely, return loss, VSWR, radiation pattern are analyzed. The FR4 substrate is used to the proposed antenna. The dimension of proposed antenna is 143mm of width and 71mm of length and the patch dimension is 29.6mm of width and 38mm of length. The return loss and VSWR of 1 X 4 array antenna is -34.8815dB and 1.012, respectively. The rectangular slots are taken in equal length and width in order to enhance the performance.